2015
DOI: 10.1051/mbcb/2015028
|View full text |Cite
|
Sign up to set email alerts
|

Difficultés d’avulsion de la troisième molaire mandibulaire incluse : place de l’orthopantomogramme

Abstract: Résumé -Objectif : L'objectif de cette étude était de mettre en exergue le rôle de l'orthopantomographie dans la prédiction des difficultés rencontrées lors de l'avulsion des troisièmes molaires incluses en utilisant l'échelle de Pederson. Abstract -Difficulties of impacted lower third molar extraction: the role of the orthopantomogram. Introduction: The orthopantomogram allows for the classification of impacted lower third molars according to depth, the spatial relationship with the ramus and the root relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous Pakistani studies also revealed that mesio-angular impaction was the most common type of impaction 15,24 . The prevalence of dental caries in the second molar adjacent to 3 rd molars has been estimated to be as less as 1% to 5% to as high as 15% to 51% in previous studies [5][6][7]15 . In our study, we also found slightly higher frequency as 61% of distal caries of 2 nd molars in the presence of impacted 3 rd molars.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous Pakistani studies also revealed that mesio-angular impaction was the most common type of impaction 15,24 . The prevalence of dental caries in the second molar adjacent to 3 rd molars has been estimated to be as less as 1% to 5% to as high as 15% to 51% in previous studies [5][6][7]15 . In our study, we also found slightly higher frequency as 61% of distal caries of 2 nd molars in the presence of impacted 3 rd molars.…”
Section: Discussionmentioning
confidence: 96%
“…Due to a lack of space or barrier, third molars are often held back during an eruption, making this area less accessible for oral hygiene practices 5,6 . If they are enclosed or embedded, they gather plaque, increasing the odds of infection in the posterior molar region 7,8 .…”
Section: Introductionmentioning
confidence: 99%